KAJIAN KESIAPSIAGAAN PENGGUNA BANGUNAN PUBLIK TERHADAP BENCANA ALAM GEMPA BUMI PADA KANTOR GUBERNUR PEMERINTAH ACEH - Faisal Faisal; Munirwansyah Munirwansyah; Eldina Fatimah (Prodi Magister Teknik Sipil Unsyiah, 2019)
The province of Aceh was struck by a massive earthquake and tsunami on Sunday, December 26, 2004. The earthquake and tsunami disaster killed 173,741 people and 116,368 people were missing. The earthquake and tsunami in Aceh Province resulted in thousands of houses and public buildings being damaged and caused almost half a million people to be refugees. This study aims to determine the level of preparedness for earthquake disasters on users of public buildings Office of the Governor of Aceh Government. This research uses survey method by distributing questionnaires to users of public buildings and observing the building of the Governor’s office of Aceh Government. The selection of samples in the field is using probability sampling method with purposive sampling technique which is the technique in determining the sample with certain considerations. Secondary data was obtained from literature review and previous research. Data processing uses analysis of validity and reliability and descriptive analysis with index frequency analysis. This study begins with the pre-survey process, where testing is conducted on the questionnaire to determine the level of validity and reliability in each item of statement tested so that the validity value is 0.312 greater than 0.3 and the reliability value is 0.613 greater than 0.6. The results of field observations have not yet fully indicated the components of public buildings that are ready to deal with earthquake. From the results of the frequency analysis the index obtained is as follows; aspect of knowledge and attitude has a score of 62% (good), aspect of policy and guidelines has a score of 66% (good), aspect of emergency response plans has a score of 65% (good), aspect of disaster warning systems has a score of 65% (good) and aspect of mobilization of resources has a score of 62% (good)